Masonic Ritual and the Display of Empire in 19th-Century India and Beyond - Simon Deschamps (Cahiers Victoriens et Edouardiens)
This article aims at exploring the role played by Freemasonry in displaying, promoting and celebrating the British Empire. It argues that Masonic lodges held centre stage in the Indian colonial public sphere. They organized processions, cornerstone laying ceremonies, and banquets on an unequalled scale, which all became an integral part of imperial display. Masonic ritual, therefore, held centre stage in the dramaturgy of colonial power in India, and also played a leading role in fostering the cult of Empire, which emerged in the last decades of the 19th century. In that respect, Freemasonry offers a stimulating venue for articulating the local and the global, the material and the cultural, formal and informal Empire. It also offers an interesting insight into imperial circulations.